IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP HAK PENANGANAN ORANG DENGAN GANGGUAN JIWA (ODGJ) BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Maudy Lexicon Nia; Wening Ken Widodasih (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Legal protection for people with mental disorders is a crucial component of fulfilling human rights and the right to health; however, in practice, discrimination, neglect, and limited mental health and rehabilitation services still persist. This study aims to examine the implementation of legal protection regarding the rights to care for PWDs based on Law No. 17 of 2023 on Health, as well as the government’s role in ensuring the fulfillment of PWDs’ rights. This study employs a normative legal research method using a legislative approach and a conceptual approach through the analysis of primary, secondary, and tertiary legal materials. The results indicate that the implementation of legal protection for ODGJ has not been optimal due to ongoing limitations in rehabilitation facilities, insufficient mental health education, low public awareness, and social stigma that hinder the fair and humane fulfillment of ODGJ’s rights. This study also shows that the government has a role in protecting the rights of people with mental health conditions through health services, rehabilitation, and education, in accordance with Law No. 17 of 2023 on health. Therefore, there is a need to enhance the government’s role in providing mental health facilities, public education, and oversight of the implementation of legal protection for people with mental disorders in accordance with statutory regulations.